User-centric Social Multimedia Computing - Sang, Jitao (Springer Theses, Recognizing Outstanding Ph.D. Research, 2014)
This book presents the first paradigm of social multimedia computing completely from the user perspective. Different from traditional multimedia and web multimedia computing which are content-centric, social multimedia computing rises under the participatory Web2.0 and is essentially user-centric. The goal of this book is to emphasize the user factor in facilitating effective solutions towards both multimedia content analysis and customized user services.